Analysis of Mn-deposits from the Alps - Stefan Delecat; Gernot Arp; Joachim Reitner (PANGAEA, 2011)
In the aftermath of the Triassic?Jurassic extinction event, extant slopes of drowned alpine reef buildups were recolonized in patches by predominantly non-rigid sponges. Just a few localities in the Northern Calcareous Alps display autochthonous communities of these rarely in situ-preserved species and provide an insight into their taphonomy. In a depression of the former Triassic reef surface at Steinplatte (Austria) lyssacinosid sponges formed spicular mats during starved Liassic sedimentation. They settled on detrital soft- or firmgrounds that were successively dominated by spicules of their own death predecessors and infiltrated sediments. Skeletal remains and adjacent micrites were partly fixed by microbially induced carbonate precipitation due to the decay of sponge organic matter. The irregular compaction of the sediment as well as volume reduction during microbialite formation resulted in syndiagenetic stromatactis cavities. Subjacent to the spiculite allochthonous sediments fill up sinkholes and crevices of the rough Triassic relief. In order to define the Lower Liassic paleoenvironment, the sediments and associated ferromanganese crusts were analysed by X-ray fluorescence and ICP-mass spectrometry. The distribution pattern of major and trace elements show usual contents of hydrogeneous Fe/Mn-precipitates. In contrast, the results of rare earth element analyses revealed a negative Cerium anomaly within the crusts and the spiculite at Steinplatte locality. In Lower Liassic sediments of the Northern Calcareous Alps such an anomaly has been proved for the first time. Most likely it is related to higher precipitation rates caused by microbial mats or possibly by a minor influx of hydrothermal fluids. Carbon and oxygen stable isotopes of the same sequence show primary signals of a small negative ?13Ccarb excursion that extends from Hettangian to Lower Sinemurian time.
Supplement to: Delecat, S et al. (2011): Aftermath of the Triassic–Jurassic Boundary Crisis: Spiculite Formation on Drowned Triassic Steinplatte Reef-Slope by Communities of Hexactinellid Sponges (Northern Calcareous Alps, Austria). In: Advances in Stromatolite Geobiology, Lecture Notes in Earth Sciences. Springer Berlin Heidelberg, 131, 355-390, https://doi.org/10.1007/978-3-642-10415-2_23